When Hitler stole pink rabbit - Judith Kerr (New York Dell, 1971)
Recounts the adventures of a nine-year-old Jewish girl and her family in the early 1930's as they travel from Germany to England.
Keywords: Refugees -- Fiction. Jews -- Germany -- History -- 1933-1945 -- Fiction. Families -- Fiction